2012
DOI: 10.5430/ijba.v3n1p93
|View full text |Cite
|
Sign up to set email alerts
|

Role of Business Management into the Success and Survival of Small Businesses: The Case of Star Learning Centre in Botswana

Abstract: The study aimed to establish the aspects of management, which have led to the survival, and success of the small-scale businesses in Botswana-a case of Star Learning Centre. The questions explored were 1) What is the role of management in the survival or success of Star Learning Centre? 2) What management styles, systems and practices are appropriate for Star Learning Centre and other small scale businesses in the Botswana? 3) What work culture is appropriate for business success? 4) What factors have enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Msamaria loans took the second position, this could be because of the longer repayment period and also because it offers a bigger amount which women could be taking to start or expand their businesses. On the other hand other women did not opt for it because it is could be viewed as too expensive hence the last resort (Mwobobia 2012, Stevenson &st-orange 2005.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Msamaria loans took the second position, this could be because of the longer repayment period and also because it offers a bigger amount which women could be taking to start or expand their businesses. On the other hand other women did not opt for it because it is could be viewed as too expensive hence the last resort (Mwobobia 2012, Stevenson &st-orange 2005.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This often happens in businesses. To (Mwobobia 2012, Makokha 2006 women have financial social demands that compete with business capital, leading to diversion of fund away from business needs. Family demands tend to drain the savings and income made by the business.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time women start their business at the age when they have family and children (Green & Cohen, 1995;Mwobobia, 2012;Zororo, 2011). The demographic results of the study showed that most of the women entrepreneurs are young and their age range from 21 to 40 years (Table 2).…”
Section: Demographic and Business Characteristicsmentioning
confidence: 99%
“…Apart from SME funding and seamless access to finance, SMEs also suffer from poor management skills which is a result of lack of adequate training and education. This results in high rates of business failure (Mohd, 2005;Mwobobia, 2012). Similarly, the support of the legal system, which can provide the needed confidence for effective practice, tends to be an issue of constant concern among SMEs in Nigeria.…”
Section: Methodsmentioning
confidence: 99%